주요우울장애 환자의 우울증상에 대한 마음챙김 기반의 치료적 개입의 효과에 관한 메타분석 - 박한뉘; 홍세연; 나의현; 임명남; 이강욱; Hannui Park; Seyeon Hong; Euihyeon Na; Myoung-Nam Lim; Kanguk Lee (Journal of the Korean Society of Biological Psychiatry, 2024)
Objectives We conducted a meta-analysis of randomized controlled trials to investigate the therapeutic effects of mindfulness-based interventions on depressive symptoms in patients with major depressive disorder. Methods In February 2021, we searched Embase, MEDLINE, Cochrane Library, PsycINFO, CINAHL, and AMED. Under the guidance of the corresponding author, two evaluators independently reviewed and selected articles based on predetermined selection criteria. Results Based on the selection criteria, we systematically screened and included a total of 12 randomized controlled trials comprising 720 cases for the final analysis. Utilizing a random-effects model for data analysis, we determined the Hedges' g value to be 0.787, indicating a medium-sized effect according to Cohen's interpretation. The 95% confidence interval for the effect size ranged from 0.414 to 1.160 (p-value < 0.0001). Conclusions This study reveals the potential effectiveness of mindfulness-based interventions in treating depressive symptoms among patients with major depressive disorder.